Comparative genomic analysis of plant-associated bacteria - Van Sluys, M. A.; Monteiro-Vitorello, C. B.; Camargo, LEA; Menck, CFM; da Silva, ACR; Ferro, J. A.; Oliveira, M. C.; Setubal, J. C.; Kitajima, J. P.; Simpson, A. J. (Annual Reviews, 2002)
This review deals with a comparative analysis of seven genome sequences from plant-associated bacteria. These are the genomes of Agrobacterium tumefaciens, Mesorhizobium loti, Sinorhizobium meliloti, Xanthomonas campestris pv campestris, Xanthomonas axonopodis pv citri, Xylella fastidiosa, and Ralstonia solanacearum. Genome structure and the metabolism pathways available highlight the compromise between the genome size and lifestyle. Despite the recognized importance of the type III secretion system in controlling host compatibility, its presence is not universal in all necrogenic pathogens. Hemolysins, hemagglutinins, and some adhesins, previously reported only for mammalian pathogens, are present in most organisms discussed. Different numbers and combinations of cell wall degrading enzymes and genes to overcome the oxidative burst generally induced by the plant host are characterized in these genomes. A total of 19 genes not involved in housekeeping functions were found common to all these bacteria.
Keywords: Bactéria; pathogen; symbiont; genome sequence; genome structure